The increase of choline acetyltransferase activity by docosahexaenoic acid in NG108-15 cells grown in serum-free medium is independent of its effect on cell growth - Machová, Eva; Málková, Barbora; Lisá, Vera; Nováková, Jana; Dolezal, Vladimír (Neurochemical research, 2006)
We investigated the influence of the polyunsaturated docosahexaenoic acid (22:6n-3; DHA) on the constitutive expression of choline acetyltransferase (ChAT) in native and induced expression in differentiated cholinergic cells NG108-15 grown in serum-free medium. Elimination of serum-derived trophic support resulted in growth arrest and a strong decrease of ChAT activity. In either conditions, DHA largely rescued general indicators of cell growth and function, and partially prevented the decrease of ChAT activity. However, the maximal effect on general cell state in native and differentiated cells, and ChAT activity in native cells, was reached at or below 10 mumol/l of DHA. In contrast, maximal induction of ChAT activity in differentiated cells required about six times higher concentrations of DHA. These data thus demonstrate stimulatory effect of DHA on ChAT activity that is independent of its general cell protective properties.
Keywords: cholin-O-acetyltransferasa; Docosahexaenoic Acids; kultivační média bez séra; buněčné dělení; Cell Line; Oxidative Stress; Culture Media, Serum-Free; lidé; buněčné linie; oxidační stres; Cell Division; Choline O-Acetyltransferase; kyseliny dokosahexaenové; Humans